Perancangan Rak Buku Modular Sekolah Dasar dengan Metode User-Centered Design (UCD) - chalik, chris; Mukti, Irsyad Khairi (Program Studi Desain Interior Unikom, 2024)
In order to support the increase of students' interest in reading and the accessibility of reading materials among students of Bhakti Winaya 2 State Elementary School, adequate and well-organized facilities are needed. However, it was found that the bookshelves available at Bhakti Winaya 2 State Elementary School at this time have not been able to meet the needs of book storage flexibly and efficiently. Therefore, it is necessary to design a modular bookshelf specifically to support library activities and facilitate students in accessing books. This research uses Mixed Methods and the User-Centered Design (UCD) approach to design bookshelves that can meet the needs of students aged 6-12 years in organizing and accessing books during library activities. The design results of this modular bookshelf show that students are more assisted in organizing and accessing book collections more easily and efficiently, especially in daily library activities. Therefore, this designed modular bookshelf can help improve the organization and accessibility of books without interfering with students' learning and reading activities.